The Authorities of Province and District Governments Regarding Spatial Planning in Aceh - Arnita; Rani, Faisal A.; Ismail, Ilyas; Efendi (International Journal of Criminology and Sociology, 2021)
Article 7 of the Law Number 11, 2006 on Aceh Governance states that the Aceh Province and districts or municipalities Governments have the authority to regulate and manage government affairs in all public sectors except for government affairs which are under the authority of the Government. It is further stated that the central authority includes government affairs of national issues that are foreign policy, defense, security, judiciary, monetary and fiscal matters, and certain affairs in the field of religion. It can be concluded that the Job Creation Act in its approach contradicts the principle of autonomy because the regulation is centralized.